Nonparticipation Selection Bias in the MOBI-Kids Study. Issue 1 (January 2019) - Turner, Michelle C.; Gracia-Lavedan, Esther; Momoli, Franco; Langer, Chelsea E.; Castaño-Vinyals, Gemma; Kundi, Michael; Maule, Milena; Merletti, Franco; Sadetzki, Siegal; Vermeulen, Roel; Albert, Alex; Alguacil, Juan; et al.
Abstract : Background: MOBI-Kids is a 14-country case–control study designed to investigate the potential effects of electromagnetic field exposure from mobile telecommunications devices on brain tumor risk in children and young adults conducted from 2010 to 2016. This work describes differences in cellular telephone use and personal characteristics among interviewed participants and refusers responding to a brief nonrespondent questionnaire. It also assesses the potential impact of nonparticipation selection bias on study findings. Methods: We compared nonrespondent questionnaires completed by 77 cases and 498 control refusers with responses from 683 interviewed cases and 1501 controls (suspected appendicitis patients) in six countries (France, Germany, Israel, Italy, Japan, and Spain). We derived selection bias factors and estimated inverse probability of selection weights for use in analysis of MOBI-Kids data. Results: The prevalence of ever-regular use was somewhat higher among interviewed participants than nonrespondent questionnaire respondents 10–14 years of age (68% vs. 62% controls, 63% vs. 48% cases); in those 20–24 years, the prevalence was ≥97%. Interviewed controls and cases in the 15- to 19- and 20- to 24-year-old age groups were more likely to have a time since start of use of 5+ years. Selection bias factors generally indicated a small underestimation in cellular telephone odds ratios (ORs) ranging from 0.96 to 0.97 for ever-regular use and 0.92 to 0.94 for time since start of use (5+ years), but varied in alternative hypothetical scenarios considered. Conclusions: Although limited by small numbers of nonrespondent questionnaire respondents, findings generally indicated a small underestimation in cellular telephone ORs due to selective nonparticipation. Abstract : Supplemental Digital Content is available in the text.